Risk-Reward in Economics: Academic Career Genealogy (UNWE Yearbook, 2024)
In academia, fostering innovation through interdisciplinary knowledge recombination is essential for growth. However, the balance between novelty and skepticism poses challenges, particularly for early-stage researchers lacking established social capital. While prior studies suggest diverse academic training enhances career prospects, this quantitative genealogical analysis challenges this notion. Drawing on the Family Tree of Trade Economists database, this study finds that having multiple supervisors and diverse academic ancestry doesn’t guarantee academic success. Surprisingly, the presence of academic siblings (shared supervisors) significantly increases the likelihood of securing a tenured position, whereas academic cousins (shared grand-supervisors) show no significant impact. This study, at the nexus of innovation and organizational management literature, informs doctoral students aiming for academic success by emphasizing the strategic choice of affiliations.